Pivotal role of MiRNA's in malignant transformation of Oral Submucous Fibrosis - J.H. Shazia Fathima; Selvaraj Jayaraman; Asma Abdullah Nurul; Ramya Sekar; Inamul Hasan Madar; Logalakshmi Thirumani; Nazmul Huda Syed (Oral Oncology Reports)
This review explores MicroRNAs' (miRNAs) role in Oral Submucous Fibrosis (OSMF) malignant transformation. OSMF, a potentially life-threatening disorder, exhibits a 7.6% to 13% probability of malignant transformation. MiRNAs like miR-21 and miR-29b play crucial roles in OSMF pathogenesis, affecting fibrosis and malignancy. Their dysregulation impacts TGF-/Smad and Wnt/-catenin signaling pathways, contributing to fibrotic alterations. OSMF malignant transformation involves genetic and epigenetic changes, with miR-34 and miR-1246 implicated in increased cell proliferation and invasiveness. MiRNAs hold diagnostic and prognostic potential in OSMF. Specific miRNA signatures correlate with disease development, aiding in individualized risk stratification. Integrating miRNA-based techniques into precision medicine offers personalized therapeutic avenues, considering ethnic and environmental factors. MiRNA-targeted therapies, potentially combined with conventional approaches, show promise in addressing OSMF complexities. However, challenges in standardization, sample variability, and off-target effects persist. Artificial Intelligence contributes to miRNA research, enhancing target prediction and understanding disease mechanisms. Continued research is crucial for identifying additional OSMF-related miRNAs and refining diagnostic and therapeutic strategies. Standardization in miRNA-based diagnostics is imperative for future implementation.